Use of low field nuclear magnetic resonance to monitor lung inflammation and the amount of pathological components in the sputum of cystic fibrosis patients. Issue 1 (1st December 2019) - Abrami, Michela; Maschio, Massimo; Conese, Massimo; Confalonieri, Marco; Di Gioia, Sante; Gerin, Fabio; Dapas, Barbara; Tonon, Federica; Farra, Rossella; Murano, Erminio; Zanella, Giada; Salton, Francesco; et al.
Abstract : Purpose: To develop a novel approach to monitor lung ventilation/inflammation in cystic fibrosis (CF) patients. Lung assessment in CF patients is relevant given that most patients succumb to respiratory failure. Respiratory functional tests (forced expiratory volume in the first second; FEV1 ) and inflammatory markers are used to test pulmonary ventilation/inflammation, respectively. However, FEV1 is effort dependent and might be uncomfortable for CF patients. Furthermore, inflammatory marker detection is costly and not rapid. To overcome these limitations, we propose the measurement, by means of low field nuclear magnetic resonance, of the spin‐spin relaxation time ( T 2m ) of water hydrogens present in CF patient sputum. In CF sputum, different biological components are pathologically increased and inversely related to lung functionality. Moreover, we showed that these components alter in a dose‐dependent manner the T 2m in synthetic CF sputum. Methods: Sputum samples were obtained from 42 CF subjects by voluntary expectoration; FEV1, C‐reactive protein (CRP), blood neutrophil counts together with cytokine (tumor necrosis factor alpha [TNFα], interleukin [IL]‐1β, IL‐4, and vascular endothelial growth factor) quantifications were then evaluated. Results: In sputum samples, we observe that T 2m directly correlates ( r FEV1 = 0.44; P < 10 −4 ; 169 samples) with FEV1 . Moreover, T 2m inversely correlates with the circulating inflammation markers CRP/neutrophil number ( r CRP = −0.44, P < 10 −4 ; r NC = −0.37, P < 2 * 10 −4 ; 103 and 86 samples, respectively) and with the sputum inflammatory cytokines TNFα/IL‐β1 ( r TNFα = −0.72, P < 10 −4 ; r IL‐1β = −0.685, P < 10 −4 ; 27 samples). T 2m variations also correspond to FEV1 values over time in defined patients. Conclusion: These findings, together with the fast, reliable, and simple determination of T 2m, make our approach a novel tool potentially usable in the real world of CF patients.